Pengelolaan Keuangan Berbasis Balanced Scorecard di SMK Nukila Kota Ternate - Abdurrahman Senuk; Fahima Nasar; Guntur A Rahman; Yetty Yetty; Nurdin I Muhammad; Irmawati A Husen (Jurnal Informasi Pengabdian Masyarakat, 2024)
BSC is a strategic management framework used by organizations or companies to measure and monitor performance from various different and balanced perspectives. This concept, which was first introduced in 1992, was created as a solution to provide a more comprehensive view of company performance. Not only focusing on financial aspects, BSC is a metric that also takes into account other perspectives, namely customers, internal processes, and learning and growth. Balanced Scorecard (BSC)-based financial management training at the Nukila Vocational School aims to improve the school's financial management capabilities in a more focused and effective manner. It is hoped that this training can help schools achieve their strategic goals, both in terms of finance, operations and educational quality. This activity is very important for schools because it can provide education regarding appropriate financial management methods in accordance with financial management targets and can see opportunities and problems that will be faced at this time